Improvement of Time Attendance Online System: Case Study in the University - Sarawan, Kamthorn; Sarnthong, Apichai; Khumla, Pornsiri; Nasinprom, Nipa (Journal of Advanced Development in Engineering and Science, 2023)
Owing to an outbreak of a novel coronavirus (COVID-19) pandemic, the university as a case study also needs to be considered that the university’s operations adopt a work from home instead of the office. To track the work and support personnel follow the social distancing rules, the problem was studied with a cause-and-effect diagram to serving guideline for new design of time attendance system which is responding to work from home policy. This research aims to design and develop a system for online time attendance and evaluate user's satisfaction for this system. The system using web application concept is developed with PHP, JavaScript, and HTML language and the MySQL database system is used for storing data. The developed system is able to take attendance from everywhere via an internet network, to specify the workplace, and to summarize the workload performed on each day. Moreover, the HR staffs can be applied system to summarize reports for individual, each faculty, and whole university. The satisfaction survey results consisting 2 parts showed that the satisfaction of educational personnel by the 110 personnel of the university was in overall at high level (= 4.23, S.D. = 0.98), and the satisfaction of HR staff by 10 personnel was in overall at high level (= 4.13, SD = 0.69). The operation was tested by using Black Box Testing, the accuracy of the system is 100%. Consequently, implementation of web application for time attendance system is appropriate and useful for this situation. Moreover, this system can be applied and developed for the other organizations.